Soluble Epoxide Hydrolase Inhibitor: A Novel Potential Therapeutic or Prophylactic Drug for Psychiatric Disorders - Ren, Qian (Frontiers in Pharmacology, 2019)
Psychiatric disorders, including depression and schizophrenia, affect millions of people worldwide. However, the precise neurobiology of psychiatric disorders remains unclear. Accumulating evidence suggests that various inflammatory processes play a key role in depression and schizophrenia, and that anti-inflammatory drugs show therapeutic effect in patients with psychiatric disorders. Epoxyeicosatrienoic acids (EETs) and epoxydocosapentaenoic acids (EDPs) have potent anti-inflammatory properties. However, these mediators are broken down into their corresponding diols by soluble epoxide hydrolase (sEH), and inhibition of sEH enhances the anti-inflammatory effects of EETs. Therefore, sEH may plays a key role in inflammation, which is involved in psychiatric disorders. Recent studies showed that levels of sEH might be involved in the pathogenesis of certain psychiatric diseases, and the sEH inhibitor shows antidepressant and antipsychotic activity. In this review, we discuss the extensive evidence of sEH as a therapeutic target for psychiatric diseases and the clinical value of sEH inhibitor as a therapeutic or prophylactic drug.